STUDI NUMERIK EFEK PERBANDINGAN PENAMBAHAN WINGTIP FENCE DAN BLENDED WINGLETTERHADAP PERFORMA AEORODINAMIKA AIRFOIL NACA 23018 - Setyo Hariyadi S.P. (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Winglet is one of the devices in airplane wing that allows wing performances without widening the wingspan. It serves to damp the vortex flow at the ends of the wing where the airflow coincide that produce turbulence. The air loop requires more energy in the plane to make stable in the air, so it definitely wasteful of fuel. Based on the pilot experience, winglet in the plane can save fuel consumption by 7% that is a huge amount of the percentage to travel in a long way. This study conducts numerical simulation using simulation software with turbulent model of k-ε realizable. The free stream of fluid flow is determined as 40 m/s (Re = 5 x 106) with angle of attack (α) = 0o, 5o, 10o and 15o. Airfoil NACA 23018 is used as specimen test applied with or without winglet. Wingtip fence with variations of forward, rearward and blended is designed as the winglet. The results show that adding winglet can reduce the vorticity magnitude in rear wing. Moreover, it can also increase the aerodynamic performances by increasing maximum CL/CD both in forward and rearward wingtip fence and also in blended winglet. The pressure distribution in the winglet model shows gradually increasing in the lower surface compared with plain wing. Keywords: airflow, wingtip fence, blended winglet, lift force, drag force